Experimental study on sloshing characteristics in a pool with stratified liquids. (April 2020) - Cheng, Songbai; Xu, Ruicong; Jin, Wenhui; Qin, Yitong; Zeng, Xiangchu; Li, Shuo; Li, Kejia
Highlights: Effect of all parameters on sloshing confirmed under liquid stratification. Limited sloshing intensity verified using different liquid or with stratification. Except injection duration, all other parameters can affect critical gas pressure. Empirical model for predicting critical gas pressure successfully developed. Fuel compaction in reactor accident with liquid stratification should be mitigated. Abstract: Investigations on the sloshing motion of a molten fuel pool are of great significance for the improved assessment of core disruptive accidents that might occur for Sodium-cooled Fast Reactors (SFR). In this work, aimed to acquire further evidence and insight for understanding the mechanisms of this motion at more realistic complicated conditions, a large number of simulated experiments are conducted newly by importing nitrogen gas into two-dimensional liquid pools of different properties (esp. including 70 cases under the condition of liquid stratification). To achieve deeper and more comprehensive understandings, various experimental parameters such as the gas-injection pressure (~4.5 bar), pool depth (~60 cm), liquid density (Idemitsu cleaning oil, purified water), depth ratio of stratified liquids and the injection duration (0.06 ~ 0.1 s), are taken. Through detailed analyses, it is confirmed that all our present experimental parameters employed can have remarkable impact on the sloshing intensity. With increasing the gas-injection pressure, the tendency of limited sloshing intensity as observed from a pure water pool in our earlier work, can be generally reproduced at current conditions (e.g. in a pool with different liquid density or with the stratification of two liquids). Except the parameter of injection duration, the remaining experimental parameters (i.e. the pool depth, liquid density and the depth ratio of stratified liquids) are verified to have an obvious influence in changing the critical gas pressure that is required to achieve the limited intensity of sloshing. Based on the knowledge obtained from experimental analyses, an empirical model is successfully established to estimate the critical gas pressure. The performed analyses in this study also imply that comparing with pure single-phase molten pool, due to the entrainment of molten fuel by the upward gas-induced flow, the degree of fuel compaction should be mitigated under the existence of liquid stratification. Experimental data and knowledge from our work will be employed for the future improved validations of fast reactor safety analysis codes in China.